40. KNOWLEDGE AND PRACTICE OF NUTRITION TO IMPROVE HEIGHT AMONG FIRST AND SECOND YEAR MEDICAL STUDENTS AT HANOI MEDICAL UNIVERSITY IN 2022 (Vietnam Journal of Community Medicine, 2025)
Objective: To assess the knowledge, nutritional practices, and related factors influencing height development among first and second year medical students at Hanoi Medical University in 2022.Subjects and methods: A cross-sectional descriptive study was conducted on 295 first and second year students from the medical doctor and bachelor programs at Hanoi Medical University. Data were collected using a self-administered questionnaire covering knowledge, nutritional practices, and height measurements.Results: 54.9% of students had good nutritional knowledge, 32.9% had moderate knowledge, and 12.2% had poor knowledge. Regarding dietary practices, 90.34% consumed milk, 83.97% consumed eggs, and 84.67% consumed high-protein foods. The rate of prolonged energy deficiency ranged from 23.81% to 31.0%, with a higher prevalence among female students.Conclusion: Nutritional knowledge and practices are closely related to students’ height. Enhancing awareness, improving nutritional practices, and increasing physical activity are crucial for improving students’ height and overall health.
Keywords: Nutritional knowledge; nutritional practices; height; medical students